(3TQM GdJSgjds - (3CHh MjGf eMeO Hf jhSa Hf Ydj GdCfOdSj GdLHGfis; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3jHOC HHGH MQha GdLQ Hbhdg (B: (3Shi GdeSJKfi HgG aefgG ef Edi BNQg T GdMQa Ef de jNJU HeG jONd Ydjg aGdCUd GdG jYed ajg s
(3BNQgG (B:s
(3jfJgi HHGH geRI GdhUd Hbhdg (B: (3hShGA cGf GdSGcf dg UhQI ai GdNW ceG eKdfG Ce djSJ dg UhQI hgh GdJfhjf bQF HVe GdJfhjf hcSQg GfJgi s
(3GdfSNI HgG MhGTs
(3HChdgG agQS HeG JVefg GdfSNI ef CHhHGs
(3hYdjgG JMHjSGf Ydi LGeY GdbQhjjf CMOgeG SfI (B867 (3hGdBNQ SfI (B1036s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs